(untitled) (Semiárida, 2020)
This study was conducted to evaluate the effect of management on species diversity in a natural grassland of the experimental area of the Rangeland Ecology Laboratory (LEPAN), Universidade Federal de Santa Maria/Rio Grande do Sul, Brazil which has been submitted to different fire and grazing regimes along 16 years. Treatments consisted of the combination of burning and grazing factors in convex and concave slope positions in a completely randomized design. Grazing was rotational with rest intervals calculated by accumulated thermal time (760 degree days) required for the expansion of four leaves of Paspalum notatum and Andropogon lateralis. Botanical composition was determined using the BOTANAL method from 2006 to 2011. Data on number (nº) of species and Shannon index were analyzed by randomization tests in an analysis of variance using MULTIV software. Grazing had the strongest (P =0.036) influence on Shannon index and number of species. There was an interaction between grazing and relief position (P =0.052) and grazing and burning (P =0.07). There was significant difference for grazing in concave slope and for grazing on burned areas. We can conclude that management history, as well as type of disturbance affects richness and diversity of species.